Selling expert knowledge: The role of consultants in Singapore's new economy - EVERS, Hans-Dieter (Institutional Knowledge at Singapore Management University, 2015)
We are currently witnessing a major transition from the old type of industrialsociety with its traditional dominance of manufacturing work and old industrialclasses to an information and knowledge-based society (Albrow and King 1981;Drucker 1994; Stehr 1994; Hannerz 1996; Baber 1998; Evers 2000, 2000a,b,c)which is believed to have the following characteristics:· Its members have attained a higher average standard of education incomparison to other societies and a growing proportion of its labour force areemployed as knowledge workers. In other words, there is a significantreduction in the number of people working in operational roles, whileemployment in professional, knowledge-based roles has risen.· Its industry produces products with integrated artificial intelligence (usuallywith the help of IT as in the case of JIT production) such as voice-recognitionsoftware and technology which is used increasingly in smart cars.